Shahid Gangalal National Heart Centre-ST-elevation Myocardial infarction Registry (SGNHC-STEMI-Registry), Nepal - Adhikari, Chandra Mani; Acharya, Kiran Prasad; Manandhar, Reeju; Sherpa, Kunjang; Tamrakar, Rikesh; Bogati, Amrit; Singh, Satish Kumar; Kansakar, Subodh; Yadav, Dharma Nath; Dhungana, Murari; Dhungel, Sachin; Baniya, Bibek; et al. (Nepalese Heart Journal, 2020)
Background and Aims: Incidence of ST-elevation myocardial infarction (STEMI) is increasing in Nepal. We aim to describe the presentation, management, complications, and outcomes of patients admitted with a diagnosis of STEMI in Shahid Gangalal National Heart Centre (SGNHC), Nepal.Methods: Shahid Gangalal National Heart Centre-ST-elevation registry (SGNHC-STEMI) registry was a cross sectional, observational, registry. All the patients who were admitted with the diagnosis of STEMI from January 2018 to December 2018 were included.Results: In this registry, 1460 patients out of 1486 patients who attended emergency were included. The mean age of patients was 60.8±13.4 years (range: 20 years to 98 years) with 70.3% male patients. Most of the patients (83.2%) were referred from other hospitals and 16.8% of patients directly attended the SGNHC emergency. During the presentation, smoking (54%) was the most common risk factor, followed by hypertension (36.6%), diabetes mellitus (25.3%), and dyslipidemia (7.8%). After admission, new cases of dyslipidemia, HTN, Impaired Fasting Glucose (IFG), and Type 2 DM were diagnosed in 682 (51.3%), 182 (20.1%), 148 (10.3%) and 95 (8.9%) respectively. At the time of presentation, 73.3% were in Killip class I and 26.3% were above Killip class II with 5.1% in cardiogenic shock. Thirty-one percent of the cases received reperfusion therapy (Primary percutaneous intervention in 25.2% and fibrinolysis in 5.8%). Inferior wall MI was the most common type of STEMI. Among the patients who underwent invasive therapy, the multi-vessel disease was noted in 46.2% cases and left main coronary artery involvement in 0.7% cases. In-hospital mortality was 6.2% with cardiogenic shock being the most common cause. Aspirin (97.8%), clopidogrel (96.2%), statin (96.4%), ACEI/ARB (76.8%) and beta-blocker (76.8%) were prescribed during discharge.Conclusion: The SGNHC-STEMI registry provides valuable information on the overall aspect of STEMI in Nepal. In general, the SGNHC-STEMI registry findings are consistent with other international data.